Implementing Social Studies Learning Strategies to Develop Social Interaction among Fourth Grade Students at MI Muhammadiyah Trimulyo - Haikal, Fiqri; Dirmawan, Eko (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to analyze the implementation of Social Studies learning strategies in developing social interaction among fourth grade students at MI Muhammadiyah Trimulyo. The study also aims to identify how interactive classroom activities encourage students’ participation, communication, cooperation, and confidence during the learning process.Methodology: This study employed a descriptive qualitative research design conducted at MI Muhammadiyah Trimulyo. Data were collected through semi-structured interviews, classroom observations, and documentation techniques involving the principal, teachers, and fourth grade students. Data validity was examined using triangulation techniques, while data analysis applied inductive qualitative analysis through data reduction, presentation, and conclusion drawing.Main Findings: Findings revealed that Social Studies learning strategies such as group discussions, collaborative assignments, and question-and-answer activities improved students’ social interaction during classroom learning. Students became more active in asking questions, answering discussions, cooperating with peers, and expressing opinions confidently. Interactive learning activities also encouraged communication, participation, and teamwork among students, creating a more active and socially supportive classroom environment.Novelty/Originality of this study: This study specifically examines the implementation of Social Studies learning strategies in developing social interaction among students at an Islamic elementary school context. Previous studies mainly focused on character education and tolerance, while this research highlights classroom interaction, collaborative learning, and communication development during Social Studies instruction at the madrasah ibtidaiyah level, contributing new insights into elementary social learning practices.